Diversifikasi Logo Dan Kemasan Produk Sebagai Strategi Branding UMKM Kerupuk Rengginang Kaisar - Oktavyan Dwi Irianto; Fatchur Rozci (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The horizontal diversification of products that has been carried out can be utilized by Ms. Wati's Rengginang Emperor Crackers UMKM for the branding of their processed products. Product diversification is one of the efforts that can be made to expand the market in order to increase the success of an UMKM. The Rengginang Emperor Crackers UMKM is one of the businesses located in Sumber Rejo Village, Kutjur Hamlet, Purwosari District, Pasuruan Regency. The purpose of product diversification is to increase profitability and expand the market for a product. The implementation method used is the learning by doing approach. The result of this logo and packaging diversification activity is a new logo and packaging for Ms. Wati's rengginang Emperor cracker UMKM.